(untitled) - Trompenaars, Fons (New York, 1998)
Many managers understand that cultural differences affect the process of doing business, but many underestimate by just how much. This book aims to dispel the idea that there is only one way to manager and encourages readers to get to know their own culture before doing business with others. The author explores the cultural extremes and the incomprehension that can arise when doing business across cultures - even when people are working for the same company. The book explains that there are five key factors or orientations that affect how people all deal with each other, do business and manage. The goal is the "transnational organization" - one in which the company can take from each country what is best, and for those who are sensitive to these differences, the opportunities are enormous. With many practical examples and case studies, this book brings insights to the dilemma of reconciling corporate consistency with local conditions as business life rapidly internationalizes. In 1991 Fons Trompenaars was awarded the International Professional Practice Area Research Award by the American Society for Training and Development (ASTD).
Keywords: Corporate culture,Comparative management,Management; Cross-cultural studies,Cross-cultural studies